A Review on Visual Features and Click Features of Content Based Image Retrieval by Ranking System: Enhancing Image Retrieval through Visual and Click Features (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The irregularity between textual features and visual substance can cause poor image list items. To take care of this issue, click features, which are more solid than textual information in defending the importance between a query and clicked images, are received in image ranking model. In any case, the current ranking model can't coordinate visual features, which are effective in refining the click-based query items. Visual features and click features are all the while used to acquire the ranking model. Click features which are more solid instead of textual information in advocating the significance among a query and clicked images, are actualized in image ranki.ng model. To accomplish the ranking model, visual and click features are utilize.